P253 Association of Defective Monocyte-Derived Macrophage Phagocytosis with Clinical Phenotypes in Stable COPD. (19th November 2012) - Singh, R; Chana, KK; Wright, LL; Garcha, DS; Kowlessar, BS; Patel, ARC; Mackay, AJ; Fenwick, PS; Donaldson, GC; Barnes, PJ; Wedzicha, JA; Donnelly, LE
Abstract : Introduction: Macrophages play an important role in clearing inhaled particles and bacteria from the lung, thus maintaining its sterility. Defective phagocytosis of bacteria has been demonstrated in both alveolar and monocyte-derived macrophages (MDMs) from COPD patients and may play a role in the aetiology of the frequent exacerbator phenotype. We hypothesised that defective phagocytosis may also be associated with lower airway bacterial colonisation (LABC) and other clinical parameters in stable COPD. Methods: Whole blood and sputa were collected from stable patients in the London COPD cohort. Stable COPD was defined as no symptom-defined exacerbations recorded on prospectively completed diary cards in the preceding four weeks and subsequent two weeks. Monocytes were isolated from the whole blood and cultured with GM-CSF (2 ng/ml) for 12 days to generate MDMs. MDM phagocytosis of fluorescently-labelled polystyrene beads, Haemophilus influenzae (HI) and Streptococcus pneumoniae (SP) was measured by fluorimetry. LABC was defined as detection of HI, SP or Moraxella catarrhalis (MC) in sputum using quantitative PCR. Results: MDMs were cultured from 26 COPD patients. 54% were male, mean age 70.0 years (SD 8.3), FEV1 predicted 55.3% (20.3), 46% were current smokers, median daily inhaled corticosteroid (ICS) dose was 1000 (640–2000) mcg (beclomethasone equivalent dose) and median exacerbation frequency per year was 1.8 (1.0–2.9) based on diary card events. Phagocytosis of HI was significantly less with increasing exacerbation frequency (p=0.002, r=–0.58, Figure 1 ), although no significant associations were demonstrated between exacerbation frequency and phagocytosis of inert beads or SP (p=0.27 and p=0.22 respectively). 13 patients (50%) with LABC did not demonstrate any significant difference in phagocytosis of either beads (p=0.29), HI (p=0.66) or SP (p=0.88) compared with non-colonised patients. There was no significant association between phagocytosis of beads, HI or SP with age, FEV1 %predicted, smoking pack year history, ICS dose or BMI (all p>0.05). Conclusion: In stable COPD patients, decreasing phagocytosis of HI was associated with increasing exacerbation frequency. Phagocytosis was not related to LABC suggesting that macrophage activity alone may not determine bacteria colonisation. Further work is needed to elucidate the mechanisms of reduced phagocytosis in COPD and its relationship to exacerbation frequency.